2011
DOI: 10.1111/j.1365-2427.2011.02688.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an invasive crayfish on trophic relationships in north‐temperate lake food webs

Abstract: Summary 1. The introduction of invasive species is one of the main threats to global biodiversity, ecosystem structure and ecosystem processes. In freshwaters, invasive crayfish alter macroinvertebrate community structure and destroy macrophyte beds. There is limited knowledge on how such invasive species‐driven changes affect consumers at higher trophic levels. 2. In this study, we explore how the invasive rusty crayfish Orconectes rusticus, a benthic omnivore, affects benthic macroinvertebrates, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 53 publications
2
36
4
Order By: Relevance
“…This result is consistent with a study by Ruokonen et al (2014) who found that macroinvertebrate density was not reduced by invasive signal crayfish in large boreal lakes. However, our results differ from those reported by Nilsson et al (2012) who found that macroinvertebrate abundance was negatively affected by invasive rusty crayfish (Orconectes rusticus) in 10 Wisconsin lakes. This discrepancy might be accounted for by the generally low abundance of crayfish in boreal lakes (CPUE typically <<10 individuals; Erkamo et al 2010, Sandström et al 2014, including our study lakes (Table S1), compared to the large catches of O. rusticus typically reported from North American lakes (Kreps et al 2012, Nilsson et al 2012.…”
Section: Discussioncontrasting
confidence: 86%
“…This result is consistent with a study by Ruokonen et al (2014) who found that macroinvertebrate density was not reduced by invasive signal crayfish in large boreal lakes. However, our results differ from those reported by Nilsson et al (2012) who found that macroinvertebrate abundance was negatively affected by invasive rusty crayfish (Orconectes rusticus) in 10 Wisconsin lakes. This discrepancy might be accounted for by the generally low abundance of crayfish in boreal lakes (CPUE typically <<10 individuals; Erkamo et al 2010, Sandström et al 2014, including our study lakes (Table S1), compared to the large catches of O. rusticus typically reported from North American lakes (Kreps et al 2012, Nilsson et al 2012.…”
Section: Discussioncontrasting
confidence: 86%
“…These results are consistent with those of a spatial comparative study by Ruokonen et al (2014) from Lake Päijänne, which found that signal crayfish affected macroinvertebrate community composition and strongly reduced species richness, and snail density and richness. Moreover, they found comparable overall macroinvertebrate densities between crayfish and noncrayfish sites in line with results in IV but in contrast with previous studies (Nilsson et al 2012, Twardochleb et al 2013. Although snail richness showed temporal stability between sites, macroinvertebrate and snail densities indicated crayfish status effects through the years studied.…”
Section: Temporal Effects Of Signal Crayfish On Littoral Macroinvertesupporting
confidence: 80%
“…Even though this contrasts with some previous studies Nilsson et al, 2012;Twardochleb et al, 2013), Ercoli et al (2015) found no differences in littoral benthic macroinvertebrate densities between smaller Finnish lakes with crayfish and without crayfish, suggesting any effect of signal crayfish on overall numerical abundance of littoral benthic macroinvertebrates in boreal lakes is probably weak.…”
Section: Discussioncontrasting
confidence: 99%